PENGEMBANGAN MEDIA MAKET BERBASIS KOTA PALEMBANG UNTUK ANAK - Efi Novitasari; Sri Sumarni; Yetty Rahelly (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
Abstract:. This research aims to produce media maket based palembang city. The development of media model based on Palembang city uses a combination of Rowntree development model and Tessmer evaluation. The Rowntree development model consists of three stages, namely the planning, development and evaluation phase. At the evaluation stage, the formative evaluation proposed by Tessmer consists of five stages: self evaluation, expert review, one-to-one evaluation, small group evaluation. Technique of collecting data using observation. The result of the expert review obtained the average value of the assessment result from the experts in the amount of 3.80 (very valid category), Phase one to one evaluation obtained the average of the results of the observation of children with media maket of 94% (very good category) .Stage small group evaluaion obtained the average result of observation on media maket 96% (very good category). From all stages that have been done then it can be concluded that the media maket declared valid, practical for child group B.Keyword: Media Development, Palembang City, Children Group B Abstrak: Penelitian ini bertujuan untuk menghasilkan media maket berbasis kota palembang. Pengembangan media maket berbasis kota palembang ini menggunakan kombinasi model pengembangan Rowntree dan evaluasi Tessmer. Model pengembangan Rowntree terdiri dari tiga tahap, yaitu tahap perencanaan, pengembangan dan tahap evaluasi. Pada tahap evaluasi dilakukan evaluasi formatif yang dikemukakan oleh Tessmer terdiri dari lima tahap, yaitu tahap self evaluation, expert review, one-to-one evaluation, small group evaluation. Teknik pengumpulan data menggunakan observasi. Hasil expert review diperoleh nilai rata-rata hasil penilaian dari para ahli pada  1 sebesar 3.80 (kategori sangat valid), Tahap one to one evaluation didapatkan rata-rata hasil observasi anak dengan media maket  sebesar 83% (kategori baik sekali).Tahap small group evaluaion didapatkan hasil rata-rata observasi pada media maket  86% (kategori baik sekali). Dari semua tahap yang telah dilakukan maka dapat disimpulkan bahwa media maket  dinyatakan valid, praktis untuk anak kelompok B.Kata Kunci: Pengembangan Media, Kota Palembang, Anak Kelompok B